Has public administration grown up? The Road to maturation - Beaumont, Enid (2004)
Public administration has not yet become adult. It exhibits many of the signs of adolescence. These signs most clearly are self-doubt and continuous adoption of the newest fad. Also the field has not come to terms with its content, so it breaks into smaller and smaller units, each with a different name considered superior to the others. Yet all have much in common. The field needs to come back together in order to move toward adulthood, which will best be realized by linking public administration and democracy. Shakespeare's call for justice seems an appropriate challenge. - Reproduced.
Keywords: Public administration